Improve, Perfect, & Perpetuate : Dr. Nathan Smith and Early American Medical Education - Hayward, Oliver S., M.D (Book collections on Project MUSE., 1998)
This is the first full-scale biography of Nathan Smith -- medical pioneer, founder of Dartmouth Medical School and cofounder of three other medical schools (Yale, Vermont, and Bowdoin), and progenitor of a long line of physicians. Smith was a central figure in early American medical education, from 1787 when he began practicing in New Hampshire, to his death in New Haven in 1829. In his day, Smith was probably the nation's leading physician, surgeon, and medical educator, and well ahead of his time in insisting that doctors practice ""watchful waiting"" and emphasizing patient-centered care. I.